2014
DOI: 10.1007/5584_2014_83
|View full text |Cite
|
Sign up to set email alerts
|

Mismatch Repair Gene Polymorphisms and Association with Lung Cancer Development

Abstract: hMLH1 and hMSH2 are two of the main members of the mismatch repair (MMR) genes family. Polymorphism of MMR genes is associated with a risk of developing sporadic and hereditary tumors. In the present case-control study, we investigated the promoter polymorphisms of selected mismatch repair genes: hMLH1 (rs1800734) and hMSH2 (rs2303425), and the risk they present regarding the development of lung cancer in the Slovak population. The study included 422 lung cancer cases, 511 controls for hMLH1 gene and 486 contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…This is better exemplified by Lynch syndrome and its increased incidence of hereditary non‐polyposis colorectal cancer (HNPCC) . In addition, studies demonstrating abnormal expression of MMR components in breast , prostate , urothelial , and lung cancers have also been described, usually showing a lower expression of MMR proteins.…”
Section: Mmr System and Your Proteinsmentioning
confidence: 99%
“…This is better exemplified by Lynch syndrome and its increased incidence of hereditary non‐polyposis colorectal cancer (HNPCC) . In addition, studies demonstrating abnormal expression of MMR components in breast , prostate , urothelial , and lung cancers have also been described, usually showing a lower expression of MMR proteins.…”
Section: Mmr System and Your Proteinsmentioning
confidence: 99%
“…No exonic SNP in MSH2 was associated with the cancer risk (see Supplementary Materials ). A recent study revealed the association between SNP rs2303425 (c.-68-50T>C), localised in 5′ UTR region, and increased risk of lung cancer (OR = 2.28, 95% CI = 1.12–4.63, p = 0.024) in a Slovak population [ 82 ]. The same study showed on 422 cases and 486 controls that rs1800734 in MLH1 was associated with increased lung cancer risk (OR = 1.40, 95% CI = 1.08–1.82, p = 0.01); the interaction between rs1800734 and rs2303425 ( MSH2 ) revealed elevated risk for genotype GG/CC (OR = 3.08, 95% CI = 1.09–8.72, p = 0.03), which was further pronounced in females (OR = 11.56, 95% CI = 1.33–100.36, p = 0.005).…”
Section: Results On Mmr Gene Variantsmentioning
confidence: 99%
“…It resulted that this specific polymorphism is associated with a higher risk of tobacco-related OSCC and could represent a useful screening marker [ 60 ]. The sample size of this study is quite low: even though a significant association of this specific SNP has been detected also for colorectal, lung and endometrial cancers [ 70 , 71 , 72 ], future larger studies (e.g., GWAS stratified by MSI status) are needed to corroborate these results.…”
Section: Msi In Head and Neck Carcinogenesismentioning
confidence: 94%